A phonological explanation to a few Huai Nan Zi Gao You commentaries. - Qiu, Ke Wei
There are precious phonological information hidden in Gao You' s ancient text commentaries. However, due to various reasons, Gao You' s commentaries are among the biggest unsolved materials in the study of historical phonology. This paper combines the achievements in Han period phonological study and modern phonetics study, together with knowledge in study of Chinese classical texts, ancient cultural and academic history, to explain some of the thousand year old unsolved word sound materials in Gao You' s commentaries. Through this study, we propose that in using phonological material from ancient texts, one needs to be equipped with the basic training in study of Chinese classical texts and Chinese cultural and historical studies. One needs to be cautious in handling materials as such, and not just by simple 'take and use' comparative method.